Poderes legislativo e executivo na internet: da construção efetiva do contribuinte nos portais, rumo à pressuposta posição de cidadão - Arten, Francisco de Assis Carvalho (2009)
This research investigates the Legislative and Executive powers in the use of information technologies, particularly the Internet, evaluating the quality of official portals, with regard to facility of use, government information, services, public control, participation and interactivity. The main purpose of empirical research is proving that, despite all the talk of politicians who bow to public communication online for closer and interactivity with citizens, this does not happen in practice. The Internet user is treated as a taxpayer and not as a citizen. The empirical research studied the public portal of the Federal Government, the Chamber of Deputies, the Government of São Paulo and Rio de Janeiro and the Legislative Assemblies. However, the empirical analysis is a specific moment in the research, which in fact occurs as demand tematize social participation, which is based on models of democracy: liberal, participatory and deliberative; it will be examinated the ways in which these models deal the public participation in things of the state. The epistemological proposal of this work aims to contribute to the development of critical studies on communication, specifically online communication. It examines the wrong use of the Internet that are turning online communication in a new avatar of the metamorphosis of the system of inequality and exclusion from the study of some aspects of the revolution made of information technology in various regions of the world. It examines also the effects of computerization and virtualization generalized processes and social relations, individuals, businesses, institutions and states, in short, a process of ciberacultureness widespread, a condition that tends to aggravate the existing pattern of social injustice, producing more inequality and exclusion an area that drew anarchic and democratic. The stratifications are already happens in these fields, establishing a new hierarchy: perverse and oppressive. It points out as the main responsible for this new social order to " estrutural recycle", the very ciberdemocracy global capitalism, which requires of each one, states or individuals, the constant recycling and cognitive growth, in a pace increasingly accelerated. This situation has caused peculiar feelings : confusion, disorientation and perplexity. This new form of colonialism and exclusion is unprecedented in actuality, in the viewing of authors such as Boaventura de Souza, Eugênio Trivinho and Zygmunt Bauman, main theoretic used in this analysis